Optimizing Smart Consumption and Green Financing Literacy Through Radio Talkshows - Junika Halawa; Tania Monica Potu (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
The implementation of Community Service (PKM) for the January 2025 period was carried out by a team from the Faculty of Economics and Business School UPH Surabaya Campus with partner Radio Sangkakala Surabaya. Therefore, Universitas Pelita Harapan Surabaya Campus collaborates with Radio Sangkakala Surabaya to be able to provide education to the community more broadly. This collaboration is built by presenting quality speakers from the Management Study Program and Accounting Study Program. Each speaker will present topics that are interesting and in accordance with current issues. Based on discussions regarding the needs of the community, this PKM is carried out by providing briefings to the community with 2 main themes on “Optimizing Smart Consumption" and Green Financing Literacy through Radio Talk Shows” which is a topic that is in demand and is being discussed. With the implementation of this interactive talk show, it is hoped that it can provide information and educational education for the wider community in the Surabaya area in terms of economics and business that can increase community knowledge and skills.